2011
DOI: 10.1177/205891581100200107
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Mongrel Dog Seminal Plasma Proteins and Their Correlation with Semen Characteristics

Abstract: The objective of this study was to characterize mongrel dog seminal plasma proteins with SDS-PAGE and to determine the correlation between different proteins and semen characteristics. Ejaculate volume, sperm motility, total sperm count, live sperm percent, percentage abnormalities and membrane integrity (hypo osmotic swelling test) were assessed in 5 ejaculates of seven dogs. For each dog, seminal plasma was also pooled from five ejaculates and proteins were separated by SDS-PAGE using polyacrylamide concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Moreover, significant correlations of two seminal plasma proteins (67 and 58.6 kDa) were found with sperm quality characteristics, and suggested to be valuable markers for fertility (De Souza et al 2007). It was demonstrated that the concentrations of 4 protein fractions (14, 24, 70 and 82 kDa) of canine seminal plasma correlated with semen quality parameters (Cheema et al 2011). Recently, it has been reported that proteins of intermediate-and low-molecular weights (ranging from 24 to 42 kDa) account for 61.3 to 74.3% of the total protein concentration in the seminal plasma of dogs (Cheema et al 2011).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Moreover, significant correlations of two seminal plasma proteins (67 and 58.6 kDa) were found with sperm quality characteristics, and suggested to be valuable markers for fertility (De Souza et al 2007). It was demonstrated that the concentrations of 4 protein fractions (14, 24, 70 and 82 kDa) of canine seminal plasma correlated with semen quality parameters (Cheema et al 2011). Recently, it has been reported that proteins of intermediate-and low-molecular weights (ranging from 24 to 42 kDa) account for 61.3 to 74.3% of the total protein concentration in the seminal plasma of dogs (Cheema et al 2011).…”
Section: Discussionmentioning
confidence: 95%
“…It was demonstrated that the concentrations of 4 protein fractions (14, 24, 70 and 82 kDa) of canine seminal plasma correlated with semen quality parameters (Cheema et al 2011). Recently, it has been reported that proteins of intermediate-and low-molecular weights (ranging from 24 to 42 kDa) account for 61.3 to 74.3% of the total protein concentration in the seminal plasma of dogs (Cheema et al 2011). Several authors reported that 12-14 kDa and 15 kDa protein fractions were enzyme arginine esterase, which could account for about 90% of the total proteins secreted by the prostate and 30% of the seminal plasma proteins in the dog (Isaacs and Coffey 1984, Dube et al 1985, De Souza et al 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The average protein content in the SP of the English Springer Spaniel dogs was higher when compared to non-breed dogs in which the results of measurements were obtained using the same method (Cheema et al 2011). The differences in the results might be related to breed determinants, although this issue requires further research.…”
Section: Discussionmentioning
confidence: 86%
“…Seminal plasma, a complex mixture of secretions originates from the testis, epididymis and accessory sex glands, modulates the fertilizing ability of spermatozoa (Russell et al, 1984;Strzeżek et al, 2005). In dogs, most of the seminal plasma components, which are implicated in the sperm function, originate in the prostatic secretion (Cheema et al, 2011). These components may break down at variable rates after semen collection due to metabolism by spermatozoa and enzyme degradation, and may vary with interval from previous ejaculation, degree of sexual excitement, and health status of accessory sex glands (Olar et al, 1983).…”
Section: Discusionmentioning
confidence: 99%